Development and performance of a rolling table used on a centrifuge. Issue 4 (3rd May 2018) - Evans, Tim; Koseki, Junichi; Aoki, Yasuo; Higuchi, Shunichi; Kishimoto, Kenichi
Abstract : This paper outlines the development and performance of a rolling table on a centrifuge for use in understanding solid bulk cargo behaviour during ocean transportation. The rolling table was designed to actuate a container with cargo mass of up to 100 kg, mimicking cargo heights up to 20 m. Roll angles up to 25° with dynamic G forces up to 30 g were achieved at scaled ship motion frequency of about 5 Hz using a centrifuge operating at a static G force of 50 g . Commissioning tests defined the operating window of the number of cycles achievable at each roll angle as well as the controllability and reproducibility of the oscillations. The rolling table was readily controlled with roll angles achieved within 1% of the aim and dynamic G forces matching the scaling requirements.